The unquiet heart - Welsh, Kaite (Welsh, Kaite. Sarah Gilchrist mystery., 2019)
Edinburgh, 1893. Sarah Gilchrist has no intention of marrying her dull fiancé Miles, the man her family hope will restore her reputation and put an end to her dreams of becoming a doctor, but when he is arrested for a murder she is sure he didn<U+2019>t commit, she finds herself his reluctant ally. Beneath the genteel façade of upper class Edinburgh lurks blackmail, adultery, poison, and madness, and Sarah must return to Edinburgh<U+2019>s slums, back alleys, and asylums as she discovers the dark past about a family where no one is what they seem, even Miles himself. It also brings her back into the orbit of her mercurial professor, Gregory Merchiston<U+2014>he sees Sarah as his protege, but can he stave off his demons long enough to teach her the skills that will save her life?